Pengaruh Profitabilitas, Likuiditas, Solvabilitas Dan Sales Growth Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di BEI) - Aulia, Astrid Amarilis; Nurhanifah, Afifa (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to examine the effect of profitability, liabilities, solvency and sales growth on firm value. Profitability using return on assets (ROA), liquidity using current ratio (CR), solvency using debt to asset ratio (DER), sales growth using sales growth calculation (SG) while firm value using price to book value (PBV). By using firm value as an independent variable, this study uses purposive sampling as a technique in sampling and multiple regression analysis as the analysis technique used. The population in this study were food and beverage companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2021 period, with a total research sample of 20 companies and 40 observation data. The results of the study were obtained from the four hypotheses, only 2 hypotheses were accepted, namely profitability and solvency had an effect on firm value. While liquidity and sales growth did not affect firm value.